Multiple rounds of speciation associated with reciprocal gene loss in polyploid yeasts. - BYRNE, KEVIN PATRICK; WOLFE, KENNETH (My University, 2006)
A whole-genome duplication occurred in a shared ancestor of the yeast species Saccharomyces cerevisiae, Saccharomyces castellii and Candida glabrata. Here we trace the subsequent losses of duplicated genes, and show that the pattern of loss differs among the three species at 20% of all loci. For example, several transcription factor genes, including STE12, TEC1, TUP1 and MCM1, are single-copy in S. cerevisiae but are retained in duplicate in S. castellii and C. glabrata. At many loci, different species have lost different members of a duplicated gene pair, so that 4-7% of single-copy genes compared between any two species are not orthologues. This pattern of gene loss provides strong evidence for speciation through a version of the Bateson-Dobzhansky-Muller mechanism, in which the loss of alternative copies of duplicated genes leads to reproductive isolation. We show that the lineages leading to the three species diverged shortly after the whole-genome duplication, during a period of precipitous gene loss. The set of loci at which single-copy paralogues are retained is biased towards genes involved in ribosome biogenesis and genes that evolve slowly, consistent with the hypothesis that reciprocal gene loss is more likely to occur between duplicated genes that are functionally indistinguishable. We propose a simple, unified model in which a single mechanism--passive gene loss-enabled whole--genome duplication and led to the rapid emergence of new yeast species.
PUBLISHED
Keywords: Human genetics